Studying brain activity during word-by-word interactions using wireless EEG - Goregliad Fjaellingsdal, Tatiana (PLoS One, 2020)
We introduce here the word-by-word paradigm, a dynamic setting, in which two people take turns in producing a single sentence. This task requires a high degree of coordination between the partners and the simplicity of the task allows us to study with sufficient experimental control behavioral and neural processes that underlie this controlled interaction. For this study, 13 pairs of individuals engaged in a scripted word-by-word interaction, while we recorded the neural activity of both participants simultaneously using wireless EEG. To study expectation building, different semantic contexts were primed for each participant. Semantically unexpected continuations were introduced in 25% of all sentences. In line with the hypothesis, we observed amplitude differences for the P200—N400—P600 ERPs for unexpected compared to expected words. Moreover, we could successfully assess speech and reaction times. Our results show that it is possible to measure ERPs and RTs to semantically unexpected words in a dyadic interactive scenario.